Pedagogy and Personalism: Fundamental References of Education between Emergencies and Search for Meaning - Marisa (Paedagogia Christiana, 2021)
Due to the problematic issues of the times into which it is projected, pedagogical reflection is at risk of losing its particularity as a theory called to preserve the perennial fundamentals of the person and education. Exerting the theoretical references of pedagogical anthropology inspired by personalism and its recovery in a hermeneutic perspective, the article outlines the specificity of pedagogy and its intrinsic relationship with the concept of the person. From the investigation emerges a ‘pedagogy of the person’ committed, especially in the contemporary context, to outlining the main ‘thematic nuclei’ to guide education: person, educability, interpretation and search for truth.